2007
DOI: 10.1097/qai.0b013e31802e298c
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of On-Line and Off-Line Sexual Risk in Men Who Have Sex With Men

Abstract: MSM recruited on-line who reported a new or casual sex partner(s) in the prior 3 months are at considerable risk of HIV or other sexually transmitted infections, but they are equally likely to report UAI whether sex partners were met on-line or off-line. The Internet may be an ideal venue for reaching high-risk MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
5
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 37 publications
13
99
5
4
Order By: Relevance
“…Finally, the results of this study may not be generalizable to all MSM. Although the demographic characteristics of the sample are consistent with other online-recruited samples of MSM (Chiasson et al, 2007;Mitchell & Horvath, 2013;Mustanski, 2007), given the disproportionate rate of HIV infection among Black MSM (Lieb et al, 2011;Prejean et al, 2011), future research should examine perceptions of prevalence among more diverse samples.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, the results of this study may not be generalizable to all MSM. Although the demographic characteristics of the sample are consistent with other online-recruited samples of MSM (Chiasson et al, 2007;Mitchell & Horvath, 2013;Mustanski, 2007), given the disproportionate rate of HIV infection among Black MSM (Lieb et al, 2011;Prejean et al, 2011), future research should examine perceptions of prevalence among more diverse samples.…”
Section: Discussionmentioning
confidence: 92%
“…Porém, uma dificuldade na comparação dos resultados para este fator é o período escolhido para investigar a quantidade de parceiros, pois os estudos apresentam uma variação muito grande (2 até 12 meses). O número médio foi de 23 parceiros nos últimos 12 meses e está muito acima do que a literatura apresenta 2,7,17,19,22 . E entre os que relataram sexo anal desprotegido com homens HIV positivos ou de sorologia desconhecida, a média foi de 26 parceiros; e os que praticaram sexo anal sem preservativo com homens de sorologia negativa tiveram em média 20 parceiros.…”
Section: Discussionunclassified
“…Na literatura, alguns estudos que investigaram as práticas e comportamentos sexuais de homens que fazem sexo com homens (HSH), os quais recrutam parceiros sexuais na internet, mostram resultados que indicam que a internet proporciona certa facilidade para o encontro de parceiros sexuais e para o sexo anal desprotegido [1][2][3][4][5][6] . Por outro lado, outro estudo 7 , comparando HSH que buscaram parcerias na internet com HSH que buscaram parcerias fora da rede, mostrou maior prevalência do sexo arriscado para HIV no último grupo.…”
Section: Introductionunclassified
“…Research among MSM who use GSN apps to find sex partners have shown mixed results regarding the relationship between GSN app use and risky sexual practices. While some studies found no association between GSN app use for partner-seeking and sexual risk behavior [11,12], some research suggests that partner-seeking on GSN apps is associated with increased condomless anal intercourse [9,13,14], drug use (i.e. methamphetamine, Viagra, poppers, painkillers) [10,13,15], number of partners [10,13,16,17], and history of STI diagnosis [15,16,[18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Though many studies have surveyed MSM to examine the use of GSN apps to find sex partners [10][11][12][13][14][15][16][18][19][20][21][22], relatively few studies have used the GSN apps' geospatial capabilities to better understand geographical patterns of partner-seeking among MSM. Previous research in Atlanta, Georgia described a methodology for using the geolocation features of a GSN app as a novel approach to calculating the estimated spatial density of GSN app-using MSM.…”
Section: Resultsmentioning
confidence: 99%